2016
DOI: 10.1080/1028415x.2016.1222332
|View full text |Cite
|
Sign up to set email alerts
|

Agaricus blazeiextract attenuates rotenone-induced apoptosis through its mitochondrial protective and antioxidant properties in SH-SY5Y neuroblastoma cells

Abstract: The present study was aimed to find out the effect of Agaricus blazei mushroom extract against rotenone-induced cellular model. SH-SY5Y neuroblastoma cells are divided into four experimental groups (control, rotenone (100 nM), A. blazei (5 μg/ml) + rotenone (100 nM), and A. blazei alone treated) based on MTT assay, cells were allowed to measure the ROS, TBARS levels, and antioxidants activities. Finally, mitochondrial transmembrane potential (MMP) and expressions of apoptotic proteins were also analyzed. Pre-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…So, it is important to explore how Pleurotus sajor caju (PSC) constituents may regulate the cell dynamics and reduce cell proliferation. Identification of isolated compounds or extracts that induce the apoptotic cascade to reduce proliferation rates of cancer cells would be an effective strategy to control cancer progression (Venkatesh Gobi et al, 2018). The aim of this study was to investigate the effect of PSC extracts, specifically the PSC n-hexane extract (PSC-hex) in the proliferation of colorectal cancer cells (HCT116 wt , -Bax , -p21 and -p53 ), and to correlate the observed anti-proliferation activity to activation of proapoptotic and/or cell arrest regulation pathways.…”
Section: Introductionmentioning
confidence: 99%
“…So, it is important to explore how Pleurotus sajor caju (PSC) constituents may regulate the cell dynamics and reduce cell proliferation. Identification of isolated compounds or extracts that induce the apoptotic cascade to reduce proliferation rates of cancer cells would be an effective strategy to control cancer progression (Venkatesh Gobi et al, 2018). The aim of this study was to investigate the effect of PSC extracts, specifically the PSC n-hexane extract (PSC-hex) in the proliferation of colorectal cancer cells (HCT116 wt , -Bax , -p21 and -p53 ), and to correlate the observed anti-proliferation activity to activation of proapoptotic and/or cell arrest regulation pathways.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that MCEE inhibits the intrinsic apoptosis pathway by alleviating mitochondrial dysfunction by oxidative stress. Several studies have supported the notion that various natural product extracts inhibit apoptosis induced by H 2 O 2 [ 32 ], rotenone [ 8 ], and glutamate [ 11 ] in human and/or rat neuronal cell lines and this has been confirmed by the increased depolarized ΔΨm, Bax/Bcl2 ratio, and cytochrome c expression and activated caspases. It has been suggested that the natural product extracts used in each study protect cells through inhibition of the mitochondrial-dependent apoptosis pathway.…”
Section: Discussionmentioning
confidence: 92%
“…When the level of depolarized ΔΨ m increases, the cytochrome c present in the mitochondrial intermembrane space is released into the cytoplasm, which activates caspase-9 by binding to apoptosis protease activating factor (APAF)-1. Activated caspase-9 activates caspase-3 and results in apoptotic cell death [ 8 , 13 , 34 , 48 ]. The mitochondria-dependent cell death cascade is regulated by the Bcl2 family.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations